Proposição de um método de gestão da satisfação dos clientes baseado na integração das normas ISO 9001, ISO/TS 16949 e NBR 15100 - Silva, Erika Cristina da (2013)
The measurement of customer satisfaction has become a process of extreme importance to organizations on the competitive landscape in which they find themselves today. For this reason, there is a variety of publications of this subject. However, few are linked or cite references to quality standards. Another relevant fact is the lack of publications on the integration of industry quality standards, with the majority only addresses the integration of ISO 9001 (Quality), ISO 14001 (Environment), OHSAS 18001 (Occupational Health and Safety) and SA 8000 (Social Responsibility). Therefore, it is concluded that there is a lack of published methods that manage the information of customer satisfaction for applications in organizations that have certificates in various industry sectors quality standards. This research included a case study in a large steel company that has the characteristics to perform it and this resulted in the proposal of a method for managing customer satisfaction consisting of 14 steps, which present practices and activities that should be undertaken by the organization. To achieve this goal it was considered the standard ISO 9001 and two industry standards (ISO/ TS 16949 and NBR 15100), a matrix for integration the satisfaction requirements of the three standards, two theoretical models for measuring customer satisfaction and the context in which the organization operates.